Age-Related and Side-Dependent Differences in Hip Range of Motion among Female Indian Athletes: Establishing Reference Values - Anbupriya, M; Meyyappan, RM (International Journal of Membrane Science and Technology, 2023)
Restricted hip mobility and flexibility are always associated with increased risk for lower extremity injury and poor athletic performance in female athletes. Reference values for hip motions in female athletes by age and sports are lacking. The primary aim of the study is to document the active and passive range of motion of hip joint among adolescent and adult Indian female athletes. Next, to compare between the sides and age group in the same population. This is a cross-sectional study involving 498 healthy female athletes of age group 15-21 years involved in the high impact sports were conveniently selected for the measurements of hip active and passive range of motion with a Universal goniometer. Participants with recent history of musculoskeletal injury and neurological pain syndromes were excluded from the study. Comparing the baseline values of active and passive range of motion of hip joint, between adolescent and adult female athletes, revealed a significant difference (p<0.05) in both dominant and non-dominant leg except for passive hip abduction (p>0.05). However, adolescents demonstrated higher hip flexion, internal rotation, and external rotation, and adults showed greater hip extension. Active and passive reference values for hip range of motion is documented for South Indian female athletes in relation to age and high impact sports. Future research involving injury prediction, prevention and rehabilitation protocol among female sports can utilize these values.